The Impact of Online Interactive Platform Services on Oral Health Behaviors in Older Adults With Mild Cognitive Impairment: Protocol for a Randomized Controlled Trial - Yin Q; Chai Z; Tao B; Liu P; Luo Y; Zhao Q; Yang B (Journal of Multidisciplinary Healthcare)
Qianyu Yin,1,2,* Zhaowu Chai,3,* Binbin Tao,1,2 Ping Liu,1,2 Yu Luo,1,2 Qinghua Zhao,4 Bing Yang1 1Department of Nursing, the Affiliated Stomatological Hospital of Chongqing Medical University, Chongqing, People’s Republic of China; 2College of Nursing, Chongqing Medical University, Chongqing, People’s Republic of China; 3Outpatient Department at Longfor Guangnian, the Affiliated Stomatological Hospital of Chongqing Medical University, Chongqing, People’s Republic of China; 4Center of Nursing Research, the First Affiliated Hospital of Chongqing Medical University, Chongqing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Qinghua Zhao, Center of Nursing Research, the First Affiliated Hospital of Chongqing Medical University, Yuzhong District, Chongqing, 400016, People’s Republic of China, Tel +86 18602308866, Email 201307@hospital.cqmu.edu.cn Bing Yang, Department of Nursing, the Affiliated Stomatological Hospital of Chongqing Medical University, Yubei District, Chongqing, 401147, People’s Republic of China, Tel +86 13228649430, Email yangb@hospital.cqmu.edu.cnPurpose: Older adults with mild cognitive impairment (MCI) are at a high risk for oral health decline. To address this, we designed an intervention to improve oral health behaviors specifically for elderly individuals with MCI. Here we describe the protocol for a study with the following aims: to enhance oral health behaviors through online education tailored to the cognitive load of older adults and to maintain or delay cognitive decline.Patients and Methods: This randomized, parallel, single-blind controlled trial will evaluate the effectiveness of an oral health behavior intervention based on an online interactive platform (e-COM[OH]) in older adults with MCI. The participants will be randomly assigned to two groups. The intervention group will receive oral health behavior training through an online platform consisting of four modules: Games, Health Knowledge, Health Skills, and Symptom Reporting Center. The control group will follow the hospital’s official account and receive general oral health education. The primary outcome will be the oral health behavior score, assessed using an oral health behavior questionnaire. The secondary outcomes will include social support, perceived stress, cognitive level, oral health-related quality of life, and oral health status. Participant enrollment will begin in April 2024 and is expected to be completed in November 2024.Conclusions: This trial will evaluate whether the e-COM(OH) WeChat mini-program is suitable to improve the oral health behaviors and cognitive functions of older adults with MCI. If its effectiveness is validated and e-COM(OH) is deemed acceptable, appropriate, and feasible, it could serve as a strategic approach to address oral health issues and prevent cognitive decline in older adults with mild cognitive impairment.Trial Registration: The trial has been registered on the www.chictr.org.cn registration platform on 19 April 2024 (registration number: ChiCTR2400083250).Keywords: aged, cognitive dysfunction, internet, oral hygiene, randomized controlled trial